Investigating the effect of substituting fractions of imported coals with coke oven tar on coke quality: pilot plant study - Makgato, Seshibe Stanford (My University, 2015)
In this study, coke oven tar addition over a range of 0 – 8 wt.% was evaluated as a possible substitute for imported coals fractions. Coke oven tar used was collected from coke oven tar decanters of the by-products section of the coke making plant. Moisture content in coke oven tar varied depending on the residence time and water carryover from coke oven tar separators to storage tanks. Therefore, various moisture ranges were considered in order to observe its effect on coal blend, carbonization and coke properties. The optimum moisture content in coke oven tar was found to be 3% with a coke oven tar addition of 6 wt.% in the coal blend. At the same coke oven tar addition of 6 wt.% in the coal blend but with 6% moisture content in coke oven tar, coke properties improved, coke yield showed up to 4% decrease. On the other hand, with 1% moisture content in coke oven tar of 6 wt.% in the coal blend, coke yield increased by 1% and low coke properties such as I40 of 42.9 and Stability of 50.3 were achieved. The latter process was characterized by excessive increased in wall pressure and pushing energy. Both wall pressure and pushing energy increase are less desirable due to their detrimental effect on the physical condition of the oven walls. Furthermore, addition of coke oven tar with 1% moisture content to coal blend can be prohibited by its high viscosity. At 3% moisture content in coke oven tar addition of 6 wt.% in the coal blend, coke properties improved. When the amount of coke oven tar was increased to 8 wt.% at the optimum coke oven addition, coke yield was not affected but low CSR of 57.8 against a target of ³60 was achieved as opposed to CSR of 65.4 at 6 wt.%. Also, coke stability of 52.2 at 8 wt.% as opposed to 56.1 at 6 wt.% was achieved. Moreover, the highest I40 of 50.9 was achieved at 6 wt.% whereas with 8 wt.% coke oven tar, I40 of 47.9 was achieved. However, up to 2% decrease in coke yield was observed. Despite this 2% decrease in coke yield, coke oven tar addition is a positive and viable option based upon economic factors (i.e. this reduces the quantity and cost of imported coals and still achieves improved coke quality which result in improved blast furnace operation and better hot metal quality).
Keywords: coal substitution, coke oven tar, coal moisture, coal blend, coke quality